Attributes of service quality – A report from Belgrade restaurants - Đurović, Mladenka; Božić, Aleksandar (Hotel and Tourism Management, 2022)
The aim of this paper is analysis of the importance of service quality attributes in the Belgrade restaurants. The data were collected on a sample of 484 respondents, users of restaurant services in Belgrade and analyzed using the statistical package STATISTIKA 5.0. Three dimensions (Staff, Food, Restaurant facility) were formed based on factor analysis. It was found that the respondents? attitudes differ depending on their gender and level of education. The findings can contribute to improving the service quality of the Belgrade restaurants through improvement of the restaurant performances in accordance with the expectations of customers. The most important improvement is to provide food of excellent taste and quality which is better than in other restaurants.